High planting density on ‘Chimarrita’ peach - Mayer, Newton Alex; Rodrigues das Neves, Tainá; Tamaine Rocha, Cláudia; Lucas da Silva, Valécia Adriana (Revista de Ciências Agroveterinárias, 2016)
The average peach yield for Rio Grande do Sul State is only 9.8 t ha-1, which is the lowest among the main six Brazilian peach producing states. One of the factors that can contribute decisively to improve productivity is to increase planting density. This research aimed to study the technical feasibility to reduce in-row spacing for ‘Chimarrita’ peach, under edaphoclimatic conditions in Pelotas, Rio Grande do Sul State, Brazil. A non-irrigated experimental field orchard was established and five tree spacing were tested: 6.3 x 1.0 m (1,587 trees ha-1), 6.3 x 1.5 m (1,058 trees ha-1), 6.3 x 2.0 m (794 trees ha-1), 6.3 x 2.5 m (635 trees ha-1) and 6.3 x 3.0 m (529 trees ha-1), in randomized blocks with four repetitions. We concluded that the planting densities tested did not affect fruit weight, transversal and longitudinal fruit diameter, and also did not affect trunk diameter, trunk cross sectional area (TCSA) and yield efficiency. However, 6.3 x 1.0 m or 6.3 x 1.5 m spacing led to significant increases in accumulated yield in the first four years of production. The higher planting density in ‘Chimarrita’ peach presents technical feasibility at adaphoclimatic conditions of Pelotas-RS, Brazil, and we recommended 6.3 x 1.0 m or 6.3 x 1.5 m spacing.